2021
DOI: 10.3389/fimmu.2021.704050
|View full text |Cite
|
Sign up to set email alerts
|

Combined Blockade of GARP:TGF-β1 and PD-1 Increases Infiltration of T Cells and Density of Pericyte-Covered GARP+ Blood Vessels in Mouse MC38 Tumors

Abstract: When combined with anti-PD-1, monoclonal antibodies (mAbs) against GARP:TGF-β1 complexes induced more frequent immune-mediated rejections of CT26 and MC38 murine tumors than anti-PD-1 alone. In both types of tumors, the activity of anti-GARP:TGF-β1 mAbs resulted from blocking active TGF-β1 production and immunosuppression by GARP-expressing regulatory T cells. In CT26 tumors, combined GARP:TGF-β1/PD-1 blockade did not augment the infiltration of T cells, but did increase the effector functions of already prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In our study, we also observed a reduction in the number of blood vessels in MC38-ST3Gal5 KO tumors, however it did not impact tumor growth. Prior research revealed that endothelial cells forming the blood vessels in MC38 tumors were distinct from endothelial cells found in the blood vasculature of CT26 tumors ( Bertrand et al. 2021 ), which might explain the differential effect of ST3Gal5 on blood vessel formation in our study.…”
Section: Discussionmentioning
confidence: 49%
“…In our study, we also observed a reduction in the number of blood vessels in MC38-ST3Gal5 KO tumors, however it did not impact tumor growth. Prior research revealed that endothelial cells forming the blood vessels in MC38 tumors were distinct from endothelial cells found in the blood vasculature of CT26 tumors ( Bertrand et al. 2021 ), which might explain the differential effect of ST3Gal5 on blood vessel formation in our study.…”
Section: Discussionmentioning
confidence: 49%
“…The principal binding partner of GARP, TGF-β, has been shown to induce the expression of PD-L1, but it remains unclear if GARP expression can as well [55,56]. It is worth noting that the simultaneous targeting of GARP, TGF-β1, and PD-1 has been shown to be an effective combination therapy, capable of restoring T effector cell function and overcoming resistance to PD-1/PD-L1 blockade [57,58]. Future studies are planned to clarify the relationship between GARP, PD-L1, and differentiation to determine if their contribution to immune suppression is responsible for the observed reduction in patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…The blocking of TGF-β1 signaling favors the proliferation and expression of adhesion molecules, such as E-selectin in ECs, leading to the densification and normalization of the vasculature within the tumors. Moreover, the co-blockade of TGF-β1/PD-1 increased the density of blood vessels covered by pericytes ( 204 ). CD4 + and CD8 + T cells effectively mediate vascular normalization in breast cancer models ( 108 , 205 ).…”
Section: Vascular Normalization and Immunotherapymentioning
confidence: 99%